Challenges of the notary in determing the honorarium making of deeds - Semmy Slamet; Habib Adjie (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to find out the problems and challenges of determining the honorarium of a notary in making a deed and the solution. This research is normative juridical research using statutory, conceptual, and case approaches. Legal materials were collected through literature study and analyzed using qualitative analysis. The results of this study indicate that there are problems in determining the honorarium for making deeds, namely 1) notaries are faced with a choice between following the organizational provisions of the Indonesian Notary Association or participating in market competition; 2) there are several notaries who end up being dragged into bargaining over the cost of making a deed which has actually been stipulated by the notary professional organization because they are more indulging their egos to get a large number of clients without considering the notary's dignity as a public official; and 3) it is necessary to stipulate rules on the minimum honorarium for Notaries, so that an equal honorarium will be formed between one Notary and another.